Kepuasan Kerja Tutor Pusat Kegiatan Belajar Masyarakat (PKBM) di Kota Pekanbaru - Hilvi Fauzan; Muhammad Jais; Eddy Noviana (CV. Rayyan Dwi Bharata, 2024)
The aim of this research is 1) to find out how high the job satisfaction of tutors is in Pekanbaru City. This type of research is descriptive with a quantitative approach. The population in this study was 63 PKBM tutors in Pekanbaru City aged 25-45. The sampling technique using Simple Random Sampling is a method of drawing from a population or universe in a certain way so that each member of the population or universe has the same opportunity to be selected or taken, using the Slovin formula, the sample is 54 tutors aged 25-45 years. Data collection method in research This is in the form of a questionnaire. The research instrument goes through several stages, namely: 1) reviewing all theories related to the variables to be studied, 2) compiling indicators for each variable, 3) compiling a grid, 4) compiling statement items and establishing a measurement scale, 5) trialling the instrument , 6) analysis of question items by testing the validity and reliability of each statement item. Data collection in this research used a questionnaire. With a total research sample of 54 people, the trial was carried out at PKBM Pekanbaru City with 30 tutors aged 25-45 years. The money was used as a trial sample, validity test with a value of rtable = 0.361 obtained from 30 tutors aged 25-45 years. Based on descriptive analysis, the mean value of job satisfaction was obtained based on each indicator it is at a mean value of 3.78 which is is at a high level. The highest indicator is colleagues with The mean value of 3.91 is in the high interpretation, then namely Bosses/Leaders with a mean value of 3.78 are in the high interpretation, wage/salary indicator with a mean value of 3.72 and indicators that have The lowest mean value is promotion with a mean value of 3.70 in the interpretation tall. The conclusion of this research explains that based on indicator, then the job satisfaction of PKBM tutors in Pekanbaru City gets a score The mean is 3.78 in the high interpretation, meaning job satisfaction for PKBM tutors in the city Pekanbaru is already relatively high.